2007
DOI: 10.1088/0953-8984/19/41/413101
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles at fluid interfaces

Abstract: Nanoparticles at fluid interfaces are becoming a central topic in colloid science studies. Unlike in the case of colloids in suspensions, the description of the forces determining the physical behavior of colloids at interfaces still represents an outstanding problem in the modern theory of colloidal interactions. These forces regulate the formation of complex two-dimensional structures, which can be exploited in a number of applications of technological interest; optical devices, catalysis, molecular electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
546
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(565 citation statements)
references
References 159 publications
14
546
0
5
Order By: Relevance
“…3(b), a line tension of À5 Â 10 À12 N is already sufficient to change the adsorption free energy minimum from À3k B T to À9k B T. This value is close to that reported by Wi et al [11] and well within the range of 10 À12 to 10 À6 N reported experimentally [31]. For models that include a line tension contribution, a discontinuous wetting transition is predicted [31], which can explain the sudden transition from adsorption to desorption of the nanoparticles when the solvent is changed from 20% to 25% pentanol. A more systematic study of the dependence of the adsorption energy on particle size would be necessary to determine the magnitude of the line tension.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…3(b), a line tension of À5 Â 10 À12 N is already sufficient to change the adsorption free energy minimum from À3k B T to À9k B T. This value is close to that reported by Wi et al [11] and well within the range of 10 À12 to 10 À6 N reported experimentally [31]. For models that include a line tension contribution, a discontinuous wetting transition is predicted [31], which can explain the sudden transition from adsorption to desorption of the nanoparticles when the solvent is changed from 20% to 25% pentanol. A more systematic study of the dependence of the adsorption energy on particle size would be necessary to determine the magnitude of the line tension.…”
supporting
confidence: 88%
“…The effects of line tension and net charge on the nanocrystals will now be briefly discussed. In contrast to microparticles, nanoparticles are expected to exhibit much stronger line tension effects, which cause an additional contribution to the adsorption energy ÁF ðhÞ ¼ ðR 2 À h 2 Þ 1=2 [31]. As shown in Fig.…”
mentioning
confidence: 99%
“…It was found that generally the line tension has a minor impact on the contact angles of particles with radius larger than ∼1 nm. 31 In this report we present NR experiments combined with the contrast variation method to in situ measure the contact angle of NPs deposited on a Langmuir-Blodgett trough at close-packed configuration and at the air-water interface. We present a new approach that enables the determination of contact angles, adsorption energies and interfacial energy differences of core-shell NPs.…”
Section: Introductionmentioning
confidence: 99%
“…16 Using molecular simulations it has been shown that macroscopic treatments can accurately predict adsorption strengths for particles as small as ~5nm, however, studies have revealed that macroscopic theories can fail in predicting the strength of interactions for smaller particles and the range of the nanoparticle/interface interactions. 17--20 For example, monitoring the free energy profile of nanoparticles at liquid interfaces, simulations have shown that the interaction between the nanoparticle and the interface (for rigid uniform spherical nanoparticles) was both longer ranged and softer than predicted by theory 17,18 due to broadening of the interface by capillary waves.…”
Section: Introductionmentioning
confidence: 99%